Molecular cloning, characterization of dax1 gene and its response to progesterone in Misgurnus anguillicaudatus. (2nd November 2019) - Huo, Weiran; Wan, Ruyan; Wang, Peijin; Zhang, Linxia; Xia, Xiaohua
Abstract: Progesterone (P4) are aquatic contaminants that can impair fish reproduction even in low concentrations. The aim of this study was to investigate the effects of P4 on the sex differentiation, by quantitative determination of transcriptional changes of a candidate target gene ( dax1, has a function in the sex determination and gonadal differentiation of several vertebrate species) in Misgurnus anguillicaudatus . We first cloned and characterized the full-length cDNAs for the dax1 in M. anguillicaudatus (designated as Ma-dax1 ). Sequence analysis reveals that Ma-dax1 shares high homology with dax1 in other species. Quantitative real-time PCR (qRT-PCR) and in situ hybridization showed that Ma-dax1 gene was highly conserved during vertebrate evolution and involved in a wide range of developmental processes including embryogenesis, central nervous system development and gonad development. For the P4 administration assay, groups of mature fish were exposed for 1, 7, 14, 21 and 28 days to nominal concentrations of 10, 100, and 1000 ng/L P4 in a flow-through system. Quantification of Ma-dax1 transcripts revealed the expression of Ma-dax1 mRNA is altered after P4 treatment in mature gonads. Those showed that P4 could influence the sexual development and sex differentiation in M. anguillicaudatus by disturbing sex differentiation-associated gene expression, and dax1 can be used as a sensitive molecular biomarker for early warning to monitor the environmental progestins chemicals in fresh water environment.